2016
DOI: 10.1016/j.ejim.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, biochemical and genetic spectrum of low alkaline phosphatase levels in adults

Abstract: Background: Low serum levels of alkaline phosphatase (ALP) are a hallmark of hypophosphatasia. However, the clinical significance and the underlying genetics of low ALP in unselected populations are unclear. Methods: In order to clarify this issue, we performed a clinical, biochemical and genetic study of 42 individuals (age range 20-77 yr) with unexplained low ALP levels. Results: Nine had mild hyperphosphatemia and three had mild hypercalcemia. ALP levels were inversely correlated with serum calcium (r=-0.38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 31 publications
4
38
2
6
Order By: Relevance
“…Furthermore, the estimated prevalence of ALPL disease-causing variants in these subjects with persistent hypophosphatasaemia was 47%. This means that one out of two subjects with persistent hypophosphatasaemia (secondary causes discarded) had HPP, which is in accordance with the study of Riancho-Zarrabeitia and coworkers [18]. More recently, the study of Mckiernan et al [19] found a higher proportion of subjects with ALPL disease-causing variants (84%), most likely because a more stringent definition of hypophosphatasaemia was used.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, the estimated prevalence of ALPL disease-causing variants in these subjects with persistent hypophosphatasaemia was 47%. This means that one out of two subjects with persistent hypophosphatasaemia (secondary causes discarded) had HPP, which is in accordance with the study of Riancho-Zarrabeitia and coworkers [18]. More recently, the study of Mckiernan et al [19] found a higher proportion of subjects with ALPL disease-causing variants (84%), most likely because a more stringent definition of hypophosphatasaemia was used.…”
Section: Discussionsupporting
confidence: 83%
“…Whatever the underlying mechanism, the data presented here support the view that p.Arg152His may be a functional variant that impairs ALP activity. Altogether, our results are consistent with previous findings of adults with persistently low levels of ALP, where 50% to 84% of individuals were found to carry coding variants in ALPL …”
Section: Discussionmentioning
confidence: 99%
“…Altogether, our results are consistent with previous findings of adults with persistently low levels of ALP, where 50% to 84% of individuals were found to carry coding variants in ALPL. (24,25) Some missense variants in ALPL have been proposed to exert dominant negative effect on enzyme function, especially those located within functional domains. (9) However, only the p. R391C variant has been tested for this in vitro with negative results.…”
Section: Discussionmentioning
confidence: 99%
“…The cohort included a total of 83 patients [age: 36 ± 22 years], 28 males and 55 females, and 28 family members, referred from 11 different hospitals from six countries: Spain (n = 45), Italy (n = 1), Russia (n = 24), Egypt (n = 4), United Arab Emirates (n = 7), and Denmark (n = 1) En tabla I aparece Portugal y Emiratos Arabes. Preliminary results of 39 of the adult patients were recently described [Riancho‐Zarrabeitia et al, ]. This project was approved by the local ethical research board and all patients or parents gave informed consent to participate in this study.…”
Section: Methodsmentioning
confidence: 99%